Buchanania lanzan fungal endophyte Penicillium sp. therapeutic properties attributed to lapachol in its extract (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Buchanania lanzan, Spr. (Family: Anacardiaceae) with known therapeutic potential is reported as vulnerable and is listed in Red Data Book of IUCN. With immense value for its bark, roots, seeds and gum, exploitation of the host on large scale is reported detrimental. Hence the authors have attempted to study the residing endophytes for metabolites equivalent to the host products. The leaf endophytic fungi were morphotyped based on internal transcribed spacer–deoxyribonucleic acid (ITS–DNA) sequences and B. lanzan endophytes identified by molecular typing include Penicillium sp, Fusarium sp., Aspergillus sp and Fusarium sp. Molecular typing identified Penicillium sp. as Penicillium gravinicasei with 98% similarity to the nearest genera and so its extract was screened for therapeutic capacities. Antioxidant activity of the extract exhibited 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging capacity with IC50 of 55.95 ± 3.29 μg.mL-1. Antimicrobial activity by disc diffusion in opposition to Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli and Bacillus subtilis significantly arrested bacterial growth. Bacterial biofilm inhibition capacity stained by acridine orange and ethidium bromide imaged by confocal laser scanning microscopy revealed bactericidal activity. Lapachol in the endophyte extract detected by TLC could support the therapeutic properties. Thus, studies on unexplored medicinal plant endophytes could pave path to identification of novel secondary metabolites as therapeutic agents and potential drug candidates.